Kinesiophobia, Pain, Muscle Functions, and Functional Performances among Older Persons with Low Back Pain. (29th May 2017) - Ishak, Nor Azizah; Zahari, Zarina; Justine, Maria
Abstract : Objectives . This study aims (1) to determine the association between kinesiophobia and pain, muscle functions, and functional performances and (2) to determine whether kinesiophobia predicts pain, muscle functions, and functional performance among older persons with low back pain (LBP). Methods . This is a correlational study, involving 63 institutionalized older persons (age =70.98 ± 7.90 years) diagnosed with LBP. Anthropometric characteristics (BMI) and functional performances (lower limb function, balance and mobility, and hand grip strength) were measured. Muscle strength (abdominal and back muscle strength) was assessed using the Baseline® Mechanical Push/Pull Dynamometer, while muscle control (transverse abdominus and multifidus) was measured by using the Pressure Biofeedback Unit. The pain intensity and the level of kinesiophobia were measured using Numerical Rating Scale and Tampa Scale of Kinesiophobia, respectively. Data were analyzed using Pearson's correlation coefficients and multivariate linear regressions. Results . No significant correlations were found between kinesiophobia and pain and muscle functions (allp > 0.05 ). Kinesiophobia was significantly correlated with mobility and balance (p = 0.038, r = 0.263 ). Regressions analysis showed that kinesiophobia was a significant predictor of mobility and balance (p = 0.038 ). Conclusion . We can conclude that kinesiophobia predicted mobility and balance in older persons with LBP. Kinesiophobia should be continuously assessed in clinical settings to recognize the obstacles that may affect patient's compliance towards a rehabilitation program in older persons with LBP.